PENERAPAN METODE ITERATIVE PADA PERANCANGAN SISTEM PEMBUKUAN PENJUALAN PT.XYZ - Akhsani Taqwiym (ISB Atma Luhur, 2020)
Bookkeeping is an activity carried out by entrepreneurs and businesspeople whose purpose is to record, document transaction activities that occur in business and business processes which then from bookkeeping results are one of the factors in decision making. Recording manually for the time being is felt to be ineffective due to the difficulty of finding transaction data, there is the possibility of human error, lack of efficient storage of documentation, and lack of management in the use of time so that interfere with performance in making bookkeeping. The solution to this problem is to change the manual method to computerized. The method used is the iteration method, application design that is designed is a database-based websitebased application. By using the iterative method, the results are in accordance with the needs and the resolution of problems that occur at PT. XYZ The purpose of designing bookkeeping sales is to be a solution to the problems that occur at PT. XYZ, helps in making notes and bookkeeping automatically, helps store data to be more time efficient and neat. The benefit of iterative reengineering is the change of the manual recording system to a new system by not disrupting the system user in carrying out the sales recordkeeping process. One of the advantages of using iterative methods is the shorter operational time and costs incurred in designing small systems when converted into requirements. From the application of the interactive method, it is obtained that the application designed can help in making notes faster and the data will be stored automatically and correctly. Data storage will be entered into books which can then be accessed by leaders and parties who need the information as needed.